A Criminal Law Approach to Illegal Deforestation in Conservation Areas - Ramadhany Nasution (Fox Justi : Jurnal Ilmu Hukum, 2025)
Illegal deforestation in conservation areas is a serious threat to the preservation of Indonesia's ecosystems and biodiversity that requires an effective criminal law approach as a protection and prevention effort. This research aims to analyze the criminal legal framework governing illegal deforestation in conservation areas and evaluate the effectiveness of criminal law enforcement in tackling the problem. The research method used is a normative juridical approach by analyzing relevant laws and regulations, court decisions, and empirical data on the implementation of forestry law enforcement in Indonesia. The results showed that Indonesia has a comprehensive criminal law framework through Law No. 5 of 1990, Law No. 41 of 1999, and Law No. 18 of 2013 which provides strict sanctions of up to 15 years in prison and a fine of Rp 15 billion, but the effectiveness of enforcement is still low due to weak coordination between agencies, limited human resources, difficulty of proof, and rampant corruption in the forestry sector. The conclusion of the study shows that although the criminal law foundation is adequate, comprehensive reforms in institutional aspects, improved coordination, application of modern technology, and eradication of corruption are needed to improve the effectiveness of criminal law enforcement in tackling illegal deforestation in Indonesia's conservation areas.